An OFDMA-Based Subcarrier and Power Allocation Scheme in Wireless Cooperative Cellular Systems - Tang, Zhihua; Zhu, Youtuan; Wei, Guo; Zhu, Jinkang (Wireless personal communications, 2009)
An OFDMA-based subcarrier and power allocation scheme is proposed in this paper in the wireless cooperative cellular system. It is assumed that users in this system have the ability to relay information to each other to improve the overall system performance. The formulation of this scheme is to maximize the uplink system throughput subject to the half-duplex, distributed power and queue state constraints of each user. A two-slot resource allocation structure is constructed to deal with the half-duplex constraint. A low-complexity suboptimal algorithm is developed to solve the problem efficiently. This algorithm first greedily allocates subcarriers and power to users and then decides the relay selection. Numerical examples demonstrate the good throughput performance of our propose scheme and the effectiveness of the low-complexity algorithm.